Differences in Perineal Wound Healing Between Doing Kegel Exercises and Not Doing Kegel Exercises - Sulala, Anis; Nikmah, Nurun (Indonesian Vocational Research Journal, 2024)
Perineal wounds are lacerations or injuries that occur along the birth canal (perineum) due to the delivery process. Wound healing is the process of replacing and repairing damaged tissue function. The purpose of this study was to see the difference in perineal wound healing between those who did Kegel exercises and those who didnot do Kegel exercises. The research method uses a Quasi-Experimental with the Posttest Only Control Group Design approach. The number of samples taken were 18 postpartum women with perineal wounds at PMB Sri Puji UW S.Tr.Keb. The sampling technique used was purposive sampling. Data collection techniques using observation sheets. Statistical test using the Mann Whitney. The results of the study after being given the treatment obtained the value of Asymp.Sig = 0.028, thus the Asymp.Sig was smaller than α <0.05, thus it can be said that there was a difference in the group that did Kegel exercises and those who did not do Kegel exercises. Because there is a significant difference, it can be said that "there is an effect of doing Kegel exercises on the healing of perineal wounds in postpartum women" at PMB Sri Puji UW S.Tr.Keb Sampang. It is hoped that the results of the research can become information for the development of health sciences, especially health in postpartum women in healing perineal wounds and reducing delays in perineal wound healing. As well as management by doing Kegel exercises to speed up the healing process of perineal wounds.